FORMATION OF STUDENTS’ KEY COMPETENCES IN SCIENTIFIC RESEARCH AND PROJECT ACTI-VITY IN THE STUDY OF PATHOPHYSIOLOGY - Hryshko, Y.M. (World of Medicine and Biology, 2013)
Priority in the professional activity of the teacher is to develop students’ core competencies by means of research and project activities. Student success in scientific research or project activity is largely determined by competent leadership in research work by the teacher. Despite the introduction in the educational process of the competency approach focuses the teacher should focus on expanding and improving student’s independent work.